Assessing quality of care among maternity waiting home users and non-users in a rural Rwandan hospital - Tayebwa, Edwin; Kalisa, Richard; Ndibaza, Amedee Fidele; van Dillen, Jeroen; Kim, Young-Mi; Stekelenburg, Jelle (Frontiers in Global Women's Health, 2025)
Maternal near-miss (MNM) and maternal death (MD) reviews may improve the quality of obstetric care. We assessed the incidence of severe maternal outcomes (SMO) and process indicators among maternity waiting home (MWH) users and non-users in a rural Rwandan hospital. We conducted a retrospective cohort study among women who were eligible for admission to the MWH (users and non-users) at Ruli Hospital in Rwanda and had delivered between January 2015 to December 2019. Using the adapted sub-Saharan Africa (SSA) MNM approach, data for each woman were collected from admission until discharge or death. There were 8,144 deliveries during the study period and 1,305 of them met the criteria for admission at the MWH. There were 326 users and 905 non-users that had live births, respectively. Overall, SMOs were more frequent among MWH non-users [122/905 (13.4%) vs. 8/326 (2.4%) for MWH users]. The leading cause of SMO was post-partum haemorrhage (PPH) (87.5% among MWH users and 45.1% among non-users), followed by sepsis and hypertensive disorders. The MNM incidence ratio was 24.5 for MWH users and 130.4 for non-users. There were four MDs among non-users (MI of 3.3%) due to coincidental conditions and other obstetric complications, and these occurred without admission to the hospital's high dependency unit (HDU). Management of PPH, sepsis and hypertensive complications was optimal. The incidence of SMO was high among MWH non-users. The quality of care in the management of the major causes of SMO was found to be optimal. However, identification and management of coincidental conditions, unanticipated complications of management, and other obstetric complications were not adequate among MWH non-users. There is a need to train health workers to improve the detection and management of these complications to improve quality of care as well as encourage the utilization of MWHs to reduce the burden due to SMO.